Islam in Japan: When an Unstoppable Force Meets an Immovable Object - Faris, Muhammad Ilyan; Ramadhan, Ananda Ilham; Triwahyu, Athaillah Arkan (Department of International Relations, Brawijaya University, 2024)
Japan’s case of inclusivity is distinctive when one considers its homogenous nature, which brings a challenge for foreign influences to integrate into its culture. However, several cases like the tolerance of Christianity in the contemporary era shows that external influences and cultures can be accepted in Japan as long as those said influences and cultures can integrate into the nation. As for Islam, its steadily growing population in Japan has raised an urgent issue in the discourse of Japan as an inclusive society. The main problem Japan had—specifically after the 9/11 attack—in regards to Islam was the biassed public perceptions which tend to generalise and stigmatise Islam and its adherents. Such perceptions were mainly caused by the few numbers of Muslims in Japan at that time and the narratives Japanese mass media brought to the public. However, recent times have seen a glimpse of light for Islam in Japan. The rising number of native Japanese that convert to Islam and the influx of refugees has counterbalanced the negative perceptions the Japanese public had prior to the current circumstances. Keywords: Islam, Islamophobia, Japan, Mass media, Inclusivity, Perception